2008
DOI: 10.1016/j.nut.2007.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary glycemic index, glycemic load, and high-sensitivity C-reactive protein

Abstract: Objective: This study examined the relation between quality of dietary carbohydrate intake, as measured by glycemic index (GI) and glycemic load (GL), and serum high-sensitivity C-reactive protein (hs-CRP) levels. Methods: During a 1-y observational study, data were collected at baseline and at each quarter thereafter. GI and GL were calculated from multiple 24-h dietary recalls (24HRs), 3 randomly selected 24HRs at every quarter, with up to 15 24HRs per participant. The hs-CRP was measured in blood samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 19 publications
1
18
0
1
Order By: Relevance
“…Prior observational studies suggested that diets high in red meat, fatty dairy products, and refined carbohydrates were associated with increased CRP [5,31], while diets high in fiber correlated with lower levels [7,31]. Some [6,28] but not all [32,33] investigators reported that a high dietary glycemic index or load was associated with increased CRP, a relationship one study found only among the women [34]. When cholesterol intakes were increased for individuals on a National Cholesterol Education Step 1 diet, CRP levels rose in the lean participants with normal glucose tolerance but not in others [35].…”
Section: Discussionmentioning
confidence: 99%
“…Prior observational studies suggested that diets high in red meat, fatty dairy products, and refined carbohydrates were associated with increased CRP [5,31], while diets high in fiber correlated with lower levels [7,31]. Some [6,28] but not all [32,33] investigators reported that a high dietary glycemic index or load was associated with increased CRP, a relationship one study found only among the women [34]. When cholesterol intakes were increased for individuals on a National Cholesterol Education Step 1 diet, CRP levels rose in the lean participants with normal glucose tolerance but not in others [35].…”
Section: Discussionmentioning
confidence: 99%
“…Another exercise‐based intervention was unable to demonstrate any reduction in CRP in diabetic or nondiabetic men despite reductions in waist circumference 24 . One recent study measuring dietary carbohydrate intake also observed no association between glycemic index or glycemic load and CRP 25 . Results from these studies question the responsiveness of CRP to follow changes in cardiovascular risk in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…24 One recent study measuring dietary carbohydrate intake also observed no association between glycemic index or glycemic load and CRP. 25 Results from these studies question the responsiveness of CRP to follow changes in cardiovascular risk in patients with diabetes. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…39 Despite the undeniable role of insulin, IGF and IGFBPs in lung cancerogenesis, an altered antioxidant/oxidant status related to a high GI and/or high GL also seems to be important in lung cancer management, also due to the fact that a large cohort study on a healthy population did not find any association between hs-CRP (an indicator of systemic inflammation) and GI or GL, which showed that another mechanism (other than a pro-inflammatory one) may be linked with metabolic alterations and a high GI or GL of diets. 41 Therefore, finding potential relationships between them in a population with lung cancer may provide additional data on the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%